Learning Style Preferences of French Learners: A Perspective from Bangladesh (Teacher’s World: Journal of Education and Research, 2024)
The objective of this research was to determine the learning style preferences of French learners in Bangladesh. A questionnaire was distributed among the French learners in different public universities and two other French language institutes across the country. Reid’s (1984) questionnaire comprises thirty learning style preference items, which are classified into six separate learning styles, i.e., auditory, visual, kinesthetic, tactile, group, and individual styles. The questionnaire is prepared to accumulate quantitative data. The researcher used five questions for the interview to collect the qualitative data. Findings of the survey reveal that visual, group, tactile, and kinesthetic learning styles were determined as major learning styles among the participants of this study. Some recommendations, like using different teaching aids such as audio-video materials and applying different techniques, have been proposed for French learners in Bangladesh.Teacher’s World: Journal of Education and Res arch, 50(1): 155-170